Orange residues in the preparation of food products: A review (Research, Society and Development, 2021)
The objective of this study was to collect and analyze publications between the years 2010 and 2020 that used orange residues in the preparation of food products. The literature review was systematic, applying the terms: “orange by-products”, “orange peel flour”, “orange albedo flour”, “orange peel fiber”, “orange pomace flour” and their combinations in Portuguese and English, in the Google Scholar, SciELO and Periódicos CAPES databases. The inclusion criteria comprised the development of food products with incorporation of orange residue, physical-chemical and/or centesimal, sensory characterization, among others. Three selection filters were defined for analysis: title and keywords, abstract and methodology, and reading. It was found 468 studies, 22 the number of articles that met the selection criteria for data collection and analysis. It was observed that the studies are relevant and varied, many products have already been prepared with orange residue: breads, cakes, cookies, pasta, jam, ice cream, hamburger and beer. The use of orange residues resulted in by-products with improvement in physical-chemical, microbiological, sensory characteristics, antioxidant capacity and bioactive compounds. It is considered that the use of orange residues is a viable alternative for the preparation of food products, with commercial potential, ensuring the appreciation of culture and the reduction of waste.